Sisters of glass - Hemphill, Stephanie (New York : Ember, 2013)
When a new glassblower arrives to help in the family business, the attraction Maria feels for him causes a web of conflicting emotions to grow even more tangled.
Booklist starred
Horn Book
School Library Journal
Booklist starred, April 2012
Horn Book, November 2012
Kirkus Review, March 2012
Keywords: Families -- Juvenile fiction; Glass blowing and working -- Juvenile fiction; Family life -- Fiction; Glass blowing and working -- Fiction; Historical fiction; Love -- Fiction; Novels in verse; Family life -- Fiction; Glass blowing and working -- Fiction; Historical fiction; Love stories; Novels in verse; Venice (Italy) -- Juvenile fiction; Venice (Italy) -- Fiction; Venice (Italy) -- Fiction; Historical fiction; Love stories; Novels in verse